Liberal thought in Argentina, 1837-1940 - Botana, Natalio R.; Gallo, Ezequiel; Barnett, Ian (Liberty Fund, 2013)
This book is a compilation of primary sources that document the history and tradition of liberalism in Argentina throughout the nineteenth and the first half of the twentieth century. With only two exceptions, none of the works have ever been translated into English before. The writings in the volume are complemented by an introduction, editorial footnotes, a chronology, and brief biographies of the authors of the original texts.